Impact of extremely immature infants on neonatal services. Issue 2 (March 1996) - Bohin, S.; Draper, E. S.; Field, D. J.
Abstract : The impact of very immature infants on neonatal services was examined within the United Kingdom. The Trent Health Region was used as a geographically defined population. Data were obtained on all infants weighing less than 1501 g at birth and all infants born before 32 weeks gestation between 1991-93. Information relating to length of stay, duration of ventilation, and survival was documented. Only one of 49 infants born before 24 weeks gestation survived. However, 75% of this group were ventilated. Most of the remaining infants died before 48 hours of age. A similar pattern was also seen in infants of 24 and 25 weeks gestation. Infants under 24 weeks gestation comprised 1.5% of all ventilated infants and consumed 2.14% of the total neonatal ventilator days for the region. It is concluded that the United Kingdom operates a conservative policy towards infants born before 24 weeks gestation and as a result resources expended on them are limited.